Buddhist Ritual from Syntax to Cognition: Insight Meditation and Homa - Payne, Richard K. (Religions, 2016)
The concept of ritual syntax is developed by relating it to cognitive studies of ritual, providing a fuller theoretical basis. Developing theoretical grounding requires differentiating between the members of five pairs of concepts: production is not the same as analysis, syntax is not the same as semantics, ritual is not the same as the mental, cognition is not the same as the mental, and syntax is not the same as language. These distinctions help avoid overly strong interpretations of the analogy between ritual and language. A discussion of ritual suggests that it is best conceptualized in terms of multiple scalar characteristics with degrees of ritualization. Two Buddhist practices, insight meditation and homa, are introduced as instances for the cognitive study of ritual. Syntax involves not simply ordering of elements, but also hierarchical organization of those elements. While syntax allows sentential elements to move within a sentence, ritual tends toward invariance. Invariance seems to contradict the claim that ritual is syntactically organized. However, rituals are often modeled on ordinary activities, producing a kind of semantic motivation for invariance.